A Analysis of Receivables Management on Cash Flow Effectiveness at PT Kimia Farma, Tbk Listed on the Indonesia Stock Exchange (IDX): Analysis of Receivables Management on Cash Flow Effectiveness at PT Kimia Farma, Tbk Listed on the Indonesia Stock Exchange (IDX) - Natasya, Evelyn Putri; Gemini, Pra; Taliding, Arianto (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to analyze the effect of receivables management on the cash flow effectiveness of PT Kimia Farma Tbk during the 2016–2023 period. Using a quantitative method with secondary data from the company's financial reports, the independent variable in this research is receivables management, measured through the receivables turnover ratio, while the dependent variable is cash flow effectiveness, measured by total cash flow. Data were analyzed using simple linear regression with SPSS 23, along with classical assumption tests to ensure model validity.The findings reveal that receivables management has a negative and significant effect on the company's cash flow effectiveness. Inefficiencies in receivables management, such as loose credit policies, slow collection cycles, or an increase in uncollectible receivables, disrupt operational cash flow. These results align with working capital management theory and previous studies, indicating that poor receivables management can reduce the availability of funds for operations, short-term liabilities, and investments.